Jerusalem stands alone - Shuqayr, Maḥmūd (Middle East literature in translation., 2018)
By turns bleak, nostalgic, and lighthearted, Jerusalem Stands Alone explores the interconnected lives of its mostly Palestinian cast. This series of quick moving vignettes tells the story of occupied Jerusalem-tales of the daily tribulations and personal revelations of its narrators. The stories, entwined around themes of family and identity, diverge in viewpoint and chronology but ultimately unite to reveal the tapestry of Palestinian Jerusalem. The settings evoke the past-churches, alleys, and people who are gone but whose spirits yearn to be remembered. The characters are sons and mothers, soldiers and wives, all of whom unveil themselves in sometimes poignant, sometimes bittersweet memories. As its history rises up through the present struggles and hopes of its people, the deepest, most personal layers of Jerusalem are revealed.